Biaryls as potent, tunable dual neurokinin 1 receptor antagonists and serotonin transporter inhibitors. Issue 15 (1st August 2015) - Degnan, Andrew P.; Tora, George O.; Han, Ying; Rajamani, Ramkumar; Bertekap, Robert; Krause, Rudolph; Davis, Carl D.; Hu, Joanna; Morgan, Daniel; Taylor, Sarah J.; Krause, Kelly; Li, Yu-Wen; et al.
Graphical abstract: Abstract: Depression is a serious illness that affects millions of patients. Current treatments are associated with a number of undesirable side effects. Neurokinin 1 receptor (NK1 R) antagonists have recently been shown to potentiate the antidepressant effects of serotonin-selective reuptake inhibitors (SSRIs) in a number of animal models. Herein we describe the optimization of a biaryl chemotype to provide a series of potent dual NK1 R antagonists/serotonin transporter (SERT) inhibitors. Through the choice of appropriate substituents, the SERT/NK1 R ratio could be tuned to afford a range of target selectivity profiles. This effort culminated in the identification of an analog that demonstrated oral bioavailability, favorable brain uptake, and efficacy in the gerbil foot tap model. Ex vivo occupancy studies with compound58 demonstrated the ability to maintain NK1 receptor saturation (>88% occupancy) while titrating the desired level of SERT occupancy (11–84%) via dose selection.